2021
DOI: 10.1055/s-0041-1728804
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Model of the Wrist Midcarpal Joint

Abstract: Background A challenge to deciphering the effect of structure on function in the wrist involves difficulty in obtaining in-vivo information. To provide a platform to study wrist mechanics using in vivo acquired forces, we developed a model of the midcarpal joint based on computed tomography (CT) scans of normal wrists. Finite element analysis (FEA) can enable application of in vivo collected information to an ex vivo model. Objectives The objectives of this study are to (1) create a three-dimensional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The structure of the midcarpal joint affects the transfer of forces through the wrist. 9,10 Recent studies have identified two distinct structural patterns of the midcarpal joint. Type 1 wrists have a lunate that has a facet with the capitate alone, while the lunate in a type 2 wrist has a facet with both the hamate and the capitate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The structure of the midcarpal joint affects the transfer of forces through the wrist. 9,10 Recent studies have identified two distinct structural patterns of the midcarpal joint. Type 1 wrists have a lunate that has a facet with the capitate alone, while the lunate in a type 2 wrist has a facet with both the hamate and the capitate.…”
mentioning
confidence: 99%
“…Type 1 wrists have a lunate that has a facet with the capitate alone, while the lunate in a type 2 wrist has a facet with both the hamate and the capitate. 11 Since the structure of the midcarpal joint affects the transfer of forces through the wrist, 9,10 we hypothesize that the way forces are transferred through the wrist will be further altered when a distal or proximal pole excision is performed. Understanding these structural and mechanical patterns may help in identifying those wrists that will be prone to develop significant midcarpal joint instability, allowing a more individualized approach to treating scaphoid nonunion and wrist arthritis.…”
mentioning
confidence: 99%